Deficits of Executive Functioning in Conduct Disorder and Attention Deficit/Hyperactivity Disorder - Hassan Shahrokhi; Mehdi Tehrani- Doost; Zahra Shahrivar; Sara Farhang; Shahrokh Amiri (Annals of Psychiatry and Treatment - Peertechz Publications, 2017)
Background: To investigates executive functioning in Conduct disorder with comorbid ADHD. Methods: Participants were adolescent males with ADHD, CD with comorbid ADHD and healthy controls. Executive functioning were assessed using Go/No go task, Iowa gambling test and selected tests from CANTAB. Results: During the SWM test, CD+ADHD group had the tendency to revisit boxes with a token compared to controls. CD+ADHD patients had a significantly higher total error compared to controls in ID/ ED set shift. They also needed more moves in SOC compared to controls and solved a signifi antly lower number of problems compared to ADHDs and controls. They had a lower delay time for choosing risky cards of Iowa. Conclusion: CD+ADHD is associated with a broad range of defi cits in executive functioning, compared to healthy controls as well as group with ADHD. ADHD group seem to have an intermediate performance compared to CD+ADHD and control groups in several measures.